Structural Transformations in Agriculture in Poland and Ukraine: Towards Economic Sustainability - HELDAK, Maria; KUCHER, Anatolii; STACHERZAK, Agnieszka; KUCHER, Lesіa (Journal of Environmental Management and Tourism, 2019)
The paper discusses the topic of production volume of selected agricultural products in Poland and in Ukraine by taking an attempt to assess the market development in the context of the general characteristics of agricultural farms in these countries. The collected information was analyzed with use of the comparative method, by juxtaposing information about the structure of agricultural farms in Poland and in Ukraine in terms of the organization of farms, their number and surface area according to the adopted area groups and the analysis of plant production according to main cultivated crops and their yield. Further factors used to evaluate the extent of changes in structural transformations in agriculture were statistical measures, including the determination coefficient. In Poland, agricultural production is conducted mainly in individual farms (also called family or private farms). This refers both to animal and plant production. On the other hand, in Ukraine, production takes place in agriculture enterprises and households, whose distribution is similar to uniform distribution. In spite of significant differences in the area covered by agricultural land in Ukraine and in Poland, the latter is characterized by a relatively high share of the production of cereal crops and sugar beet, while Ukraine is the leader in the production of sunflower seeds (second largest manufacturer in the world), which is only a marginal crop in Poland.